The Australian Nons-Profit Sector, Knowledge Management and Social Media - Rathi, Dinesh; Given, Lisa M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
This poster presents key emerging findings from the online survey which was conducted with a large number of Australian non-profit sector units to get insight into the use of knowledge management (KM) practices as well as the use of social media such as Facebook, YouTube and Twitter, particularly in KM practices. The findings from the data collected during the first month of opening of survey will be presented in the poster. These findings will provide us with better understanding KM, NPO and social media landscape which will have implications and learning for NPOs operating in Canada and other countries. Cette affiche présente les principaux résultats issus de l’enquête en ligne qui a été menée auprès d’un grand nombre d’unités australiennes du secteur à but non lucratif afin d’obtenir une perspective sur l’utilisation et les pratiques en gestion des connaissances (GC) ainsi que l’utilisation des médias sociaux tels que Facebook, YouTube et Twitter, en particulier dans les pratiques de gestion des connaissances. Les résultats des données recueillies pendant le premier mois de l’ouverture de l’enquête seront présentés sur cette affiche. Ces résultats nous fourniront une meilleure compréhension du paysage de la GC, des OSBL et des médias sociaux, ce qui aura des répercussions et un apprentissage pour les OSBL en exploitation au Canada et dans d’autres pays.